PERILAKU KECURANGAN AKADEMIK PADA MAHASISWA AKUNTANSI POLITEKNIK NEGERI BANDUNG - Hendi Rohendi (Jurusan Akuntansi Politeknik Negeri Bandung, 2018)
Abstract: This study aims to determine the academic fraud behavior form that occurred among accounting students of Bandung State Polytechnic. The type of research is quantitative with descriptive statistic method. This study uses 100 students as sample drawn from the D-IV accounting, D-IV government accounting, and D-III accounting study program. The results showed that academic fraud behavior of accounting students of Bandung State Polytechnic are in several criteria: those who never do are 54%, those who rarely do are 44%, those who sometimes do is 2% and those who frequently and always commit fraudulent behavior in academic terms is 0%. Based on the form of academic cheating behavior, the most common is the act of forgery..Keywords: Academic Fraud Behaviour, Accounting Student and Bandung State Polytechnic.